Arrest Functions of the MIF Ligand/Receptor Axes in Atherogenesis - Tillmann, Sabine; Bernhagen, Jürgen; Noels, Heidi (Frontiers in Immunology, 2013)
Macrophage migration inhibitory factor (MIF) has been defined as an important chemokine-like function (CLF) chemokine with an essential role in monocyte recruitment and arrest. Adhesion of monocytes to the vessel wall and their transendothelial migration are critical in atherogenesis and many other inflammatory diseases. Chemokines carefully control all steps of the monocyte recruitment process. Those chemokines specialized in controlling arrest are typically immobilized on the endothelial surface, mediating the arrest of rolling monocytes by chemokine receptor-triggered pathways. The chemokine receptor CXCR2 functions as an important arrest receptor on monocytes. An arrest function has been revealed for the bona fide CXCR2 ligands CXCL1 and CXCL8, but genetic studies also suggested that additional arrest chemokines are likely to be involved in atherogenic leukocyte recruitment. While CXCR2 is known to interact with numerous CXC chemokine ligands, the CLF-chemokine MIF, which structurally does not belong to the CXC chemokine sub-family, was surprisingly identified as a non-cognate ligand of CXCR2, responsible for critical arrest functions during the atherogenic process. MIF was originally identified as macrophage migration inhibitory factor, but is now known as a potent inflammatory cytokine with chemokine-like functions including chemotaxis and leukocyte arrest. This review will cover the mechanisms underlying these functions, including MIF’s effects on LFA1 integrin activity and signal transduction, and will discuss the structural similarities between MIF and the bona fide CXCR2 ligand CXCL8 while emphasizing the structural differences. As MIF also interacts with CXCR4, a chemokine receptor implicated in CXCL12-elicited lymphocyte arrest, the arrest potential of the MIF/CXCR4 axis will also be scrutinized as well as the recently identified role of pericyte MIF in attracting leukocytes exiting through venules as part of the pericyte 'motility instruction program'.